Long sentenced women prisoners: Rights, risks and rehabilitation - Genders, Elaine (Punishment & society, 2022)
This paper re-examines critically the role of rehabilitative interventions for a seriously neglected group of prisoners: women serving long sentences. Drawing on empirical research conducted in a democratic therapeutic community in a women’s prison in the south of England, it considers how far established criticisms identify insuperable difficulties that exacerbate existing harms and inequalities. It argues that evidence can be adduced to support rehabilitative interventions that are not predominantly concerned with the reduction of criminal risk but which provide tangible benefits to the personal wellbeing of women in prison and may increase their prospects of integration post release. It explores how such rehabilitative policies and practices could be supported and protected from attrition by penal power, by embedding them within a doctrine of human rights. By challenging and replacing prevalent assumptions and justifications that uphold existing power relations in prisons, we argue that a specific duty of care, owed by the prison service to women serving long sentences, can protect, support and re-imagine their right to rehabilitative opportunities.